Steroid-Induced Hyperglycemia and Its Effect on Outcomes of R-CHOP Chemotherapy for Diffuse Large B-Cell Lymphoma - Kristjanson, Mark; Lambert, Pascal; Decker, Kathleen M.; Bruin, Sonja; Tingey, Elizabeth; Skrabek, Pamela (Current oncology (Toronto), 2023)
Large doses of steroids are integral to R-CHOP, a first-line systemic therapy for diffuse large B-cell lymphoma (DLBCL), an aggressive form of non-Hodgkin Lymphoma (NHL). Patients on R-CHOP often develop clinically significant hyperglycemia from steroids. There is evidence of harms from steroid-induced hyperglycemia in the context of chemotherapy which are associated with a reduction in overall survival. The objective of our study was to characterize the effect of steroid-induced hyperglycemia on the outcomes of R-CHOP chemotherapy for DLBCL. Methods: We performed a retrospective chart review of 188 patients with DLBCL treated with R-CHOP through CancerCare Manitoba (CCMB) from 1 January 2010 to 31 December 2014. Patients diagnosed with DLBCL were identified using the Manitoba Cancer Registry. The CCMB electronic medical record was reviewed to examine the association between steroid-induced hyperglycemia and subsequent infection, including febrile neutropenic events and overall survival (OS). Results: Patients who developed hyperglycemia with steroid exposure became hyperglycemic during their first R-CHOP cycle. No significant differences in OS or rates of infection were found between euglycemic and hyperglycemic subjects. Conclusions: Patients destined to develop steroid-induced hyperglycemia declare themselves early in the course of steroid exposure. No statistically significant reduction in overall survival attributable to steroid-induced hyperglycemia was found.